Design and Development of a New Wideband CPW Fed Patch Antenna for Wireless Communication - Purnima Sharma; P. Bhattacharya (EAI Endorsed Transactions on Internet of Things, 2019)
The present work shows a compact size coplanar waveguide (CPW) fed antenna for ultra-wideband (UWB)communication. The designed antenna has a dimension of 20 × 20 × 1.5 mm3. The proposed antenna design comprises of aslotted rectangular patch etched on an inexpensive FR4 substrate. The proposed antenna offers a good impedancematching over a frequency range of 5.7 – 8 GHz. The characteristic parameters such as return loss, VSWR, radiationpattern and input impedance are analyzed using HFSS 11.0. Designed antenna is fabricated and tested. This antenna isfound to be appropriate for various IoT based applications.